Increased forage protein through corn and legume intercropping - Baghdadi, Ali; Abd Halim, Mohd Ridzwan; Othman, Radziah; Mohammad Yusoff, Martini (2014)
The quality of forage corn feed can be improved by intercropping corn with legumes. Nutritive value and yield of corn as a sole crop was compared with that of corn with intercrops of two grain legumes; soybean (Glycine max) and mungbean (Vigna radiata) and one forage legume, stylo (Stylosanthes guianensis). Four treatments comprising of corn monocrop and intercrops of corn with each of the three legumes were compared in a randomized complete block design and replicated four times. Corn-legume forage was evaluated on the basis of its nutritional value. Near infrared reflectance spectroscopy technology (NIRS) using a global calibration equation was employed to estimate nutritive quality of forage corn. Corn-legume forage intercrop dry matter (DM) yield, crude protein (CP) content and protein yield (PY) were influenced by the grain and forage legumes. The data indicated that corn-soybean intercropped treatment produced highest total DM yield which was similar to those of monocropped corn with 14.10 and 14.08 t/ha respectively. Corn-soybean mixtures gave higher protein yield than other corn-legume combination and corn sole cropping. The highest value of CP (16.70%) was observed for corn-soybean mixed forage while the lowest value (12.05%) was recorded for sole corn. Results indicate that corn-soybean intercrop can provide forage quality advantages without affecting yield.